Strategi AKU-GPP dalam Pembelajaran Sejarah Masa Pendudukan Jepang: Meningkatkan Keterampilan Berpikir Kausalitas Siswa SMAN 7 Malang - Munir, Miftakhul; Widiadi, Aditya Nugroho; Agung, Dewa Agung Gede; Wijaya, Daya Negri (Universitas Hamzanwadi, 2025)
History learning in the Merdeka Curriculum aims to develop critical thinking skills, national identity, and historical reflection through the active role of students (student-centered). However, in practice, one-way transfer still limits historical thinking skills, especially in the aspects of causality, chronological context, and present-day relevance. The results of the analysis of students in class XI-8 SMAN 7 Malang showed a lack of substantive knowledge related to the Japanese Occupation in Indonesia. As a solution, the Analysis, Knowledge, Understanding-Game Point Poster (AKU-GPP) strategy was developed, which consists of three stages: (1) Analysis to explore the causes of events; (2) Knowledge to reinforce historical facts; and (3) Understanding integrated with Game Point Poster to understand its contemporary impact. This research uses a descriptive qualitative method with observation, questionnaires, interviews, and documentation. The results show that the AKU-GPP strategy effectively improves students' causality thinking skills, active participation, affective attitudes, communication skills, observation, and reflection, so that it can be an alternative to student-centred history learning.